PENGARUH MODEL PEMBELAJARAN SCRAMBLE BERBANTUAN MEDIA CANVA TERHADAP KEMAMPUAN MEMBACA PERMULAAN DALAM PEMBELAJARAN BAHASA INDONESIA KELAS II SDN 3 BLANG MANGAT - Aisyah Ma’awiyah; Rahmy Zulmaulida; Mutiara Sani (STKIP Subang, 2026)
Indonesian language instruction at SD requires appropriate models and media so that students' reading skills can develop to their full potential. One effective model is the Scramble model, which is combined with Canva media. The purpose of this study is to understand the impact of using the Scramble model with Canva media on students' ability to learn Indonesian in class II SD Negeri 3 Blang Mangat. This study uses a quantitative approach with a quasi-experimental design and a pre-test, post-test control group design. Students in grade II SD Negeri 3 Blang Mangat make up the population and study sample. Data collection is done using the ability to read permulaan, while data analysis uses statistical methods to test hypotheses. The study's findings indicate that the experimental class's rata-rata posttest score of 88.05 is higher than the control class's score of 76.42. According to uji hipotesis, thitung > ttabel (4,381 > 1,687) based on the nilai thitung sebesar 4,381 and ttabel sebesar 1,687. If the 2-tailed Nilai Sig. is less than 0.000, then H0 is rejected and Ha is accepted. As a result, there is a significant impact of using the Scramble model with Canva media on students' ability to learn Indonesian in grade II SD Negeri 3 Blang Mangat. This model is more effective than conventional teaching because it can create engaging, creative, and innovative learning environments.